2013
DOI: 10.1016/j.rbmo.2013.07.009
|View full text |Cite|
|
Sign up to set email alerts
|

A survey of 1700 women who formed their families using donor spermatozoa

Abstract: This paper reports the results of an online survey of 1700 recipients of donor spermatozoa conducted by the Donor Sibling Registry, aiming to understand the perspectives of respondents who had used donor spermatozoa. The survey examined: choice of sperm bank and donor; reporting of births and genetic disorders; disclosure; contact with donor and half-siblings; regulation of sperm donor activity and genetic testing; and access to medical information. The respondents formed three groups: single women; women in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
0
22
1
Order By: Relevance
“…The donor's 'nonexistence' and 'medical objectification' were replaced by gratitude and esteem, as well as curiosity about his physical resemblance. This was when mothers were more likely to experience the 'donor as a kind man', hinting to his altruistic motivation (Ravelingien et al, 2014;Sawyer et al, 2013;Zadeh et al, 2016), and prepare themselves for the future offspring's wishes for ancestral connection and need to know 'the other side of their own biology' (Eva, biological mother, open-identity donation). It is like they put aside their fears and uncertainties and took into account the meaning to their child of being a donor's offspring.…”
Section: Discussionmentioning
confidence: 99%
“…The donor's 'nonexistence' and 'medical objectification' were replaced by gratitude and esteem, as well as curiosity about his physical resemblance. This was when mothers were more likely to experience the 'donor as a kind man', hinting to his altruistic motivation (Ravelingien et al, 2014;Sawyer et al, 2013;Zadeh et al, 2016), and prepare themselves for the future offspring's wishes for ancestral connection and need to know 'the other side of their own biology' (Eva, biological mother, open-identity donation). It is like they put aside their fears and uncertainties and took into account the meaning to their child of being a donor's offspring.…”
Section: Discussionmentioning
confidence: 99%
“…There is little information about the attitudes of gamete and embryo donors and recipients towards donor genetic screening. A recent on-line survey of women who had used donor sperm found support for the implementation of more comprehensive genetic screening of donors [ 15 ]; however there are also concerns amongst health professionals about the effectiveness of expanded genetic screening protocols and the need to treat donors as ‘interested stakeholders, not merely as providers of genetic material’ [ 2 ]. In this research we aimed to explore the experiences and attitudes of gamete and embryo donors and recipients towards current donor genetic screening practices and towards potential future expanded donor genetic screening.…”
Section: Introductionmentioning
confidence: 99%
“…They found that, although most of the general public preferred donors not to be paid (58%), 52% of the potential recipients were in favour. A more recent study by Sawyer et al (2013) questioned 1700 female recipients of donor sperm (including singles, lesbian and heterosexual mothers). Of the 1528 respondents to this particular question, 81% was explicitly pro-payment.…”
Section: Introductionmentioning
confidence: 99%